Development of WLAN Topology Display System - Olarn Wongwirat; Supannada Chotiphan; Tadchapon Hongtong; Nattawat Suttijumnong (My University, 2023)
Currently, packet sniffer tools can capture packets and provide information for monitoring, analyzing, and troubleshooting networks, e.g., traffic, bandwidth, protocol, etc. However, these tools lack the capability, or feature, to display a network topology diagram on the screen, particularly for a WLAN (Wireless Local Area Network), which is different from expensive network monitoring software sold commercially in the market. Therefore, it is difficult for a network administrator to visualize which client is connected to which AP (Access point) in the service areas of WLAN, or hotspots, for monitoring. This paper presents the development of the WLAN topology display system to support the network administrator in monitoring and enhancing the network services in the future. The system acquires the packet data captured by the packet sniffer tool, i.e., Wireshark. Then, the packet information is analyzed by using the data from the MAC (Medium Access Control) header following the IEEE802.11 standard to find the types, connection modes, and MAC addresses. Finally, the mapping table associated with the connected devices, i.e., client stations and APs, is constructed and used to create the WLAN topology diagram to display on the screen. The prototype system is implemented and tested in the laboratory environment, and the WLAN topology diagram showing the connections between the clients and the APs can be displayed on screen accurately as required.
Keywords: Wireless Networks and Protocols; Mobile Ad Hoc Networks; Opportunistic and Delay-Tolerant Networks